1997
DOI: 10.1093/infdis/175.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Perinatal Human Immunodeficiency Virus (HIV) Type 1 Infection Using HIV RNA Amplification and Detection

Abstract: Early diagnosis of perinatally transmitted human immunodeficiency virus type 1 (HIV) infection can guide early interventions. HIV coculture and DNA polymerase chain reaction (DNA-PCR) detect few HIV-infected infants at birth and 90%-100% by age 3 months. Because extracellular HIV RNA may appear soon after infection, a plasma HIV RNA assay was compared with DNA-PCR for early detection of perinatally infected infants. Blood-draw specimens (108) obtained at the same time from 49 HIV-infected infants and 10 specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 11 publications
1
31
0
3
Order By: Relevance
“…65,67 HIV-1 RNA assays have been assessed to be at least as sensitive as, or more sensitive than, HIV-1 DNA assays among young infants. 52,59,[66][67][68]71 Similarly high specificity by 6 to 12 weeks of age (as compared with HIV-1 DNA assays or HIV-1 culture) has been observed among nonbreastfed infants. 52,59,65,68,72 HIV-1 RNA assays are now commonly used to diagnose HIV-1 infection in infants.…”
Section: Hiv-1 Naatsmentioning
confidence: 95%
See 1 more Smart Citation
“…65,67 HIV-1 RNA assays have been assessed to be at least as sensitive as, or more sensitive than, HIV-1 DNA assays among young infants. 52,59,[66][67][68]71 Similarly high specificity by 6 to 12 weeks of age (as compared with HIV-1 DNA assays or HIV-1 culture) has been observed among nonbreastfed infants. 52,59,65,68,72 HIV-1 RNA assays are now commonly used to diagnose HIV-1 infection in infants.…”
Section: Hiv-1 Naatsmentioning
confidence: 95%
“…These assays are available as "standard" or "ultrasensitive" assays, and the lower limit of detection possible when using the ultrasensitive assays is in the range of 50 to 75 HIV-1 copies per mL of plasma. Numerous studies of the use of HIV-1 RNA assays for the diagnosis of HIV-1 infection in pediatric populations have been conducted, 52,59,[65][66][67][68][69][70][71][72][73][74][75] with the reported sensitivity of testing (Table 3) for such assays ranging from 25% to 50% within the first few days of life to 100% by 6 to 12 weeks of age. 65,67 HIV-1 RNA assays have been assessed to be at least as sensitive as, or more sensitive than, HIV-1 DNA assays among young infants.…”
Section: Hiv-1 Naatsmentioning
confidence: 99%
“…The assay requires only an enzyme immunosorbent assay washer, a reader, a heat block, and an incubator, as opposed to the thermocycler required by nucleic acid technologies. We evaluated the sensitivity and specificity of this assay for early-infancy diagnosis of HIV infection using stored plasma specimens from HIV-exposed infants of 0 to 180 days of age from two U.S. cohorts: the North Carolina Children's AIDS Network cohort (9-11) (n ϭ 154) and the New York City Pediatric AIDS Collaborative Transmission Study (PACTS) cohort (1,4,13,28,29) (n ϭ 648). Selection criteria included sufficient volume to perform the testing.…”
mentioning
confidence: 99%
“…The viral loads of HIV-infected infants may start out low at birth and increase over time (13). Therefore, a more sensitive HIV PCR test can lead to earlier, more accurate diagnosis (14), which can minimize the occurrence of We have demonstrated that the TaqMan HIV-1 Qual Test version v2.0 has increased sensitivity compared to the previously determined sensitivity for the v1.0 assay (15).…”
Section: Discussionmentioning
confidence: 82%